2006
DOI: 10.1381/096089206776944913
|View full text |Cite
|
Sign up to set email alerts
|

A Case-Controlled Matched-Pair Cohort Study of Laparoscopic Roux-en-Y Gastric Bypass and Lap-Band<SUP>®</SUP> Patients in a Single US Center with Three-Year Follow-up

Abstract: When patients are matched with 3-year follow-up according to time of surgery, age, sex and BMI, LRYGBP provides superior weight and co-morbidity reduction and can be done without severe complications. However, the LAGB is an effective weight loss tool and not every patient wishes to have the LRYGBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(68 citation statements)
references
References 12 publications
5
61
0
2
Order By: Relevance
“…103 Weight loss outcomes consistently favor RYGB by a margin of ≈25% and show persistence to 5 years postoperatively (EWL, 47% versus 67%; P<0.001), 104 with correspondingly superior rates of diabetes, hypertension, and hyperlipidemia remission for RYGB than LAGB patients at 3 years. 105 SG is a gastric volume reduction procedure that is growing in popularity and is slightly more technically demanding. The weight loss offered by SG is superior to that of LAGB at 3 years (66% versus 48% EWL; P=0.0025), but the severity of early complications is greater than with LAGB.…”
Section: Comparison Among Bariatric Proceduresmentioning
confidence: 99%
“…103 Weight loss outcomes consistently favor RYGB by a margin of ≈25% and show persistence to 5 years postoperatively (EWL, 47% versus 67%; P<0.001), 104 with correspondingly superior rates of diabetes, hypertension, and hyperlipidemia remission for RYGB than LAGB patients at 3 years. 105 SG is a gastric volume reduction procedure that is growing in popularity and is slightly more technically demanding. The weight loss offered by SG is superior to that of LAGB at 3 years (66% versus 48% EWL; P=0.0025), but the severity of early complications is greater than with LAGB.…”
Section: Comparison Among Bariatric Proceduresmentioning
confidence: 99%
“…We omitted complications whose incidence was < 0.1%. The calculated incidence of complications associated with laparoscopic bariatric surgery, obtained from the case series, 4,8,10,17,28,38,44,45,52,74,77,82,83,91,120 is summarized in Table 1; complications associated with DBS studies are shown in Table 2. 6,7,9,12,16,20,26,27,31,37,39,47,[55][56][57][58][59][60][61]64,[67][68][69]71,78,80,81,84,[86][87][88][89][96]…”
Section: Resultsmentioning
confidence: 99%
“…Although we combined short-and long-term complication rates, other studies have demonstrated that complications occurring within 30 days of surgery are more common after LRYGB, 17,120 whereas bariatric complications after 30 days are more common after LAGB; 10,45,91 port problems and band slippage, rather than the surgical placement of the band, are the most likely reasons for delayed reoperation. 17,120 Nevertheless, the superiority of LRYGB in terms of weight loss overshadows differences in complication rates when considering the overall success of LAGB versus LRYGB, as supported by the decision analysis model and several systematic reviews. 11,29,111 Decision analysis is necessarily limited by the assumptions on which the final model is based.…”
mentioning
confidence: 99%
“…When gastric bypass and adjustable gastric banding have been compared, reports have cited greater weight loss and comorbidity resolution with gastric bypass at early time intervals (1-3 years), 44,45 but similar weight loss efficacy at later (5 year) time intervals. 33 Despite difficulties in comparison of studies which report results from cohorts differing in weight and comorbidity status, adjustable gastric banding seems to be a technically safer operation with lower mortality risk than other procedures, 33 principally related to the lack of risk of intestinal leakage and subsequent sepsis early after operation.…”
Section: The Modern Era Of Bariatric Surgical Procedures For Adolescentsmentioning
confidence: 99%